An Analysis On The Teaching Strategy In Speaking Skill At Sman 2 Tembilahan - Roza, Mila; Mustajib, Agus; Syafrizal, Syafrizal (Jurnal Edukasi, 2023)
This study aims to find out what strategies are often used by teachers at SMAN 2 Tembilahan. The researcher found the problems is the strategies used by the teachers in teaching speaking at SMAN 2 Tembilahan have not been identified. The researcher chose SMAN 2 Tembilahan as the research location because the researcher saw that during PPL, the students’ ability in speaking was good and only a few students were somewhat low in speaking. The design of this research is descriptive research. The population of this study is English teachers at SMAN 2 Tembilahan. The sample for this study are two English teachers. To obtain data, researcher used interview and questionnaire as instruments, for interviews 5 question and for questionnaire 13 questionnaire. The researcher found strategies that are often used by teachers in teaching speaking. There are five strategies used by teachers in teaching speaking namely role play, storytelling, reporting, presentation and discussion group.